2020
DOI: 10.3390/antiox9060495
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Biological Activities of the Nord-West Romanian Wild Bilberry (Vaccinium myrtillus L.) and Lingonberry (Vaccinium vitis-idaea L.) Leaves

Abstract: This study was performed to evaluate and compare the in vitro antioxidant, antimicrobial, and antimutagenic activities, and the polyphenolic content of the Nord-West Romanian wild bilberry (Vaccinium myrtillus L.) and lingonberry (Vaccinium vitis-idaea L.) leaves from three different natural habitats (Smida, Turda, Borsa). In the case of both species, the flavanols level was higher in Smida habitat (altitude 1100 m), whereas quercetin derivates were more abundant in Borsa habitat (altitude 850 m). The bilberry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
51
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(90 citation statements)
references
References 79 publications
4
51
1
Order By: Relevance
“…The pronounced presence of various phytonutrients with antioxidant function strongly indicates that the bilberry extracts as a whole might also aid in the reduction in oxidative stress, despite the fact that the implicated coping mechanisms at cellular level are currently scarcely documented. Some already existing research data accentuate the antioxidant feature of bilberry extracts largely attributed to the rich anthocyanin content of bilberries [2][3][4][5][6][7]. Moreover, the in vitro antioxidant property of the assessed three bilberry extracts is further substantiated by the DPPH free radical scavenging assay, suggesting once again the superiority of the hydro-methanolic extract (E3) over the other formulations (Table 2).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The pronounced presence of various phytonutrients with antioxidant function strongly indicates that the bilberry extracts as a whole might also aid in the reduction in oxidative stress, despite the fact that the implicated coping mechanisms at cellular level are currently scarcely documented. Some already existing research data accentuate the antioxidant feature of bilberry extracts largely attributed to the rich anthocyanin content of bilberries [2][3][4][5][6][7]. Moreover, the in vitro antioxidant property of the assessed three bilberry extracts is further substantiated by the DPPH free radical scavenging assay, suggesting once again the superiority of the hydro-methanolic extract (E3) over the other formulations (Table 2).…”
Section: Discussionmentioning
confidence: 85%
“…The chemo-mapping of our extracts offers new insights into their composition, as to our knowledge, the previously reported bilberry extracts were highly focused on the anthocyanin content [2][3][4][5][6], rather than the complete phytochemical profile ( Table 1). The identified chemical classes ( Figure 2) are in agreement with reported composition of Vaccinium myrtillus L. extracts (Table S5) [35][36][37][38][39][40][41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), are well known for their health-protective properties and potential use in the treatment of urinary tract infections and chronic diseases, associated with free radicals damage in the human body. Fruits and leaves of this plant are considered to be a good source of phenolic compounds, which ensure various mechanisms of the antioxidant defense system [ 1 , 2 ]. Major groups of lingonberry’s phenolic compounds are monophenols (prevalent in leaves), anthocyanins (prevalent in fruits), phenolic acids, flavonols, catechins, and proanthocyanidins, found in both raw materials [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The formation and accumulation of bioactive compounds in the fruits are influenced by several factors, such as genotype, environmental conditions, ripeness, and storage [ 37 , 40 , 41 , 42 ]. Moreover, phenolic compounds are particularly sensitive to environmental stress, and their content changes rapidly under the influence of stress [ 43 ]. Furthermore, recent studies have shown that the levels of anthocyanins, chlorogenic acid, and quercetin were influenced by the blueberry cultivar, as well [ 34 , 44 ].…”
Section: Introductionmentioning
confidence: 99%